Exploring the meso-territorialization of third sector administration and welfare delivery in federal and union states: Evidence and theory-building from the UK. Issue 2 (15th March 2022) - Chaney, Paul; Sophocleous, Christala; Wincott, Daniel
ABSTRACT: The international trend of state restructuring and the rise of decentralized welfare systems means a key challenge for social research is to systematically explore the breadth of factors shaping the territorialization of third sector welfare delivery at the meso level in federal and union states. We address this lacuna by synthesizing historical-institutionalism and critical realism with Salamon and Anheier's classic framework on civic infrastructure development to produce an inductive analytical model for wider empirical testing. Its application here to the longitudinal case study data covering Wales shows it to be effective in providing a holistic understanding of the temporal and spatial processes underpinning decentralization. The wider significance of the case study lies in underlining the iterative, reciprocal relationship between governance reforms and territorialization – and showing how territorialization can originate in response to national crises and welfare demand caused by state and market failure in the delivery of public goods.